Effects of applying electric and magnetic fields on laser drilling. Issue 9 (June 2016) - Lu, Yi; Sun, G.; Wen, D.; Zhang, Y.; Feng, A.
Abstract To reduce defects and improve the quality of laser drilling, the electric and magnetic (EM) field-assisted laser drilling has been tested. For different industrial applications, we performed microlaser drilling and macro-through-hole drilling under different EM fields using two different lasers (ns and ms). Drilling was performed on a custom apparatus that can produce static and rotating EM fields. The motion of the plasma strongly affected the drilling quality. In an EM field, both the ns and ms lasers produced holes with smaller diameters, better surface quality, and fewer hole wall defects. The drilling defects were mainly caused by the plasma-based multi-shock effect. The EM field can influence the motion of the plasma and minimize defects.